THE ROLE OF NATIONAL IDEOLOGY IN THE DEVELOPMENT OF THE COUNTRY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article discusses the fact that the national ideology of our country unites all layers of the population and calls them to action for the common good and a single goal.